If it's not what You are looking for type in the equation solver your own equation and let us solve it.
t+1.3/2=-1.5
We move all terms to the left:
t+1.3/2-(-1.5)=0
We add all the numbers together, and all the variables
t+1.5+1.3/2=0
We multiply all the terms by the denominator
t*2+1.3+(1.5)*2=0
We add all the numbers together, and all the variables
t*2+4.3=0
Wy multiply elements
2t+4.3=0
We move all terms containing t to the left, all other terms to the right
2t=-4.3
t=-4.3/2
t=-2+0.3/2
| 58+3x-8=8x | | (x=3) | | 3-1x=5-3x | | 2×45+5x=175 | | 6(9x+2)=54x-8 | | 16=7-4n-5n | | 350=(x+20)(x-5) | | -4(6+x)=-116 | | 15=6x-9+6 | | 4(v+42)=–96 | | 6x–5=10 | | 5x/45=125 | | 3x-6+5x-10=80 | | 3(y-1)=7y+1-2(-3y-5) | | x/9=18/36 | | 45+5x=175 | | 7s-24=59 | | 2(w+7)=-3(5w-3)+2w | | -4x-5+10=13 | | 138=-2+7(-3v+8) | | 7s—24=59 | | 2x1=3x-2 | | 9(j−93)=45 | | 13^5/4x=8 | | 13x5/4x=8 | | 56=8(q+2) | | 2w+14=-13w+9 | | 2(3x+4)+86=9x+5-3x+89 | | 2/3(9x-12)=10(x+2) | | 7/5x+1=0 | | 9y-8+2(2y+4)=-5(y+3) | | 0.66x−3=11 |